A General Pattern and Implications Across All Cases. Issue 157 (25th March 2018) - Williams, David Dwayne
Abstract: Williams illustrates a general pattern he found across all the evaluators he interviewed by quoting briefly from each evaluator's story. He also explores possible implications for evaluators and their stakeholder audiences.